Sebarang Pembangun Subgrup Siklik Dari Suatu Grup (Zn,+) - Indra Bayu Muktyas; Samsul Arifin (Jurnal Matematika MANTIK, 2018)
(Zn,+) is a group of the integer modulo n with an addition operation. A cyclic subgroup is a subgroup that is generated by one element of a group. In group (Zn,+), any cyclic subgroup can be determined through a generator which is a factor of n. The aim of this article is to get all generator of the cyclic subgroup of a group (Zn,+) using Python. The result of our study shows that by using Python, for any cyclic subgroup of (Zn,+) , we can get all their generator.